Greater hemodynamic stresses initiate aneurysms on major cerebral arterial bifurcations - Guo, Hao; Liu, Jian-Feng; Li, Cong-Hui; Wang, Ji-Wei; Li, Hui; Gao, Bu-Lang (Frontiers in Neurology, 2023)
To retrospectively investigate the hemodynamic stresses in initiating aneurysm formation on major cerebral arterial bifurcations with the computational fluid dynamics (CFD) analysis.The cerebral 3-D angiographic data of the major cerebral arterial bifurcations of the internal carotid, middle cerebral, anterior cerebral and basilar arteries in 80 patients harboring bifurcation aneurysms and 80 control subjects with no aneurysms were retrospectively collected for CFD analysis of hemodynamic stresses associated with aneurysm formation.The bBifurcation angles at the major bifurcations in all patients were positively significantly (P < 0.001) correlated with age. At the center of direct flow impingement (CDFI) on the bifurcation wall, the total pressure was the highest but dropped rapidly towards branches. The wWall shear stress, dynamic pressure, strain rate and vorticity were the least at the CDFI but rose quickly to the greatest values towards branches. The bifurcation angle was significantly (P<0.001) enlarged in patients with than those with no bifurcation aneurysms for all the major arterial bifurcations. Most aneurysms leaned towards the smaller arterial branch or towards the arterial branch which formed a smaller angle with the parent artery, where the hemodynamic stresses increased significantly (P<0.05) compared with those on the contralateral arterial branch forming a larger angle with the parent artery. Following aneurysm development, the aneurysm dome hemodynamic stresses all decreased significantly (P ＜ 0.001) compared with those of at the initiation site on the bifurcation wall after virtual aneurysm removal. With decrease of bifurcation angles, the hemodynamic stresses all decreased.Formation of intracranial aneurysms on the major intracranial artery arterial bifurcations is significantly associated with and is to reduce the locally abnormally-augmented hemodynamic stresses.